(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
Introduction: According to the Indonesia Health Profile in 2023, the majority of Family Planning participants use injections (35.3%), followed by pills (13.2%). The use of Long-Term Contraceptive Methods are implant (10.5%), and IUD (8.9%). The use of Long-Term Contraceptive Methods is lower compared to short-term contraceptive methods. Objective: To determine the relationship between age, education, occupation, and the selection of Long-Term Contraceptive Methods. Method: This study used an analytical survey with a cross-sectional design. The population consisted of Fertile Age Couples, and a sample of 65 respondents was selected using the accidental sampling technique. Data was collected through interviews with a questionnaire. Data analysis included univariate and bivariate analysis with the chi-square test. Results: The majority of respondents were aged 20-35 years (69.2%), most were high school graduates (44.6%), and the majority were unemployed (83.1%). There was no significant relationship between age (p-value 0.082), education (p-value 1.000), employment (p-value 0.082) and the choice of Long-Term Contraceptive Methods. Conclusion: No relationship was found between age, education, and occupation with the selection of Long-Term Contraceptive Methods in Bukittinggi City in 2024. Keywords: Age, Ecucation, Occupation , Long-Term Contraceptive Methods